2014
DOI: 10.5603/ep.2014.0052
|View full text |Cite
|
Sign up to set email alerts
|

Przedposiłkowe i poposiłkowe zmiany stężeń obu form greliny u osób otyłych i nieotyłych

Abstract: Introduction: The potentially differential roles of both forms of ghrelin in obesity are undefined, and little is known about desacyl ghrelin's (DAG) regulation by meals. We aimed to assess changes in acyl ghrelin (AG) and DAG in response to mixed-meal consumption in obese and non-obese subjects. Material and methods: Venous blood for plasma glucose, AG and DAG assays were collected in both groups after an overnight fast and two hours after the consumption of a standard 300 kcal-mixed meal (Nutridrink, Nutrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our findings are in line with previous studies exhibiting that total plasma ghrelin was lower in individuals with both hypertension and obesity in comparison to those obese or healthy control ( 19 ). According to our data, the decrease in total ghrelin of centrally obese, hypertensive women was largely accounted by the reduction of UnAG, which is the predominant form of circulatory ghrelin ( 34 ). Only main effect of hypertension was observed on AG, suggesting that hypertension is sufficient to reduce the level of AG, regardless of the presentation of central obesity.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings are in line with previous studies exhibiting that total plasma ghrelin was lower in individuals with both hypertension and obesity in comparison to those obese or healthy control ( 19 ). According to our data, the decrease in total ghrelin of centrally obese, hypertensive women was largely accounted by the reduction of UnAG, which is the predominant form of circulatory ghrelin ( 34 ). Only main effect of hypertension was observed on AG, suggesting that hypertension is sufficient to reduce the level of AG, regardless of the presentation of central obesity.…”
Section: Discussionmentioning
confidence: 58%
“…It was reported by Barazzoni that obese people with metabolic syndrome have a higher acyl/desacyl ratio [ 7 ]. However, in our earlier study we found the opposite – the fasting AG/DAG ratio was significantly higher in non-obese controls than in obese non-diabetic patients [ 6 ]. In spite of those discrepancies, it is not explained how bariatric procedures modulate the AG/DAG ratio [ 23 ].…”
Section: Discussionmentioning
confidence: 78%
“…The MGB procedure appeared to reduce fasting acyl ghrelin levels and provided effective weight reduction in those patients. Prader-Willi syndrome is known to be characterized by the presence of hyperghrelinemia, and simple obesity is associated with reduced ghrelin levels [ 2 , 6 ]. According to available data we demonstrated for the first time that levels of both ghrelin isoforms (in the fasting state as well as prandial) did not change in a year of observation after MGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly recognized that UnAG plays crucial roles in metabolism. Fasting UnAG has been demonstrated to be significantly higher in normal healthy subjects when compared to individuals with MetS risk factor such as central obesity ( Dardzinska et al, 2014 ). In a 2-week clinical trial, single daily injection of AZP-531, an UnAG agonist, decreased body weight from baseline in obese subjects ( Allas et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%